La prescripción de las infracciones en el Derecho Administrativo Sancionador peruano - Ayvar Ayvar, Ricardo; Borda Gianella, Waldo (Pontificia Universidad Católica del Perú, 2019)
Prescription is a critical legal construct in Peruvian punitive administrative law, since it establishes a limit to the the punitive power of the State, which provides the citizens the legal certainty that they need when engaging with the public administration. Although most administrative procedures are regulated by a general norm, it is also necessary to consider the impact of specific norms on this institution.The author analyzes this topic by, first, addressing the legal status and typology of prescription to further adopt a stance regarding its legal framework. At last, the author refers to the materiality of its exceptional circumstances: the interruption and suspension of the limitation period.

La prescripción es una figura jurídica de especial relevancia para el Derecho Administrativo Sancionador debido a que permite limitar el ius puniendi del Estado frente al administrado, quien precisa de seguridad jurídica para desarrollar sus actividades.Aunque la norma general aplicable es la Ley del Procedimiento Administrativo General, también es preciso evaluar la incidencia de las normas específicas respecto de la prescripción.El autor inicia este análisis definiendo la naturaleza jurídica y tipología de la prescripción para, posteriormente, emitir un juicio crítico respecto de su tratamiento según las normas generales y específicas.Finalmente, expone la aplicabilidad de sus circunstancias especiales: interrupción y suspensión.
The prescription of administrative infractions in Peruvian Punitive Administrative Law
Keywords: Prescripción; Acto administrativo; Derecho administrativo sancionador; Interrupción; Suspensión; https://purl.org/pe-repo/ocde/ford#5.05.01